Estrategias publicitarias en Comercial Llerena de la ciudad de Babahoyo en el año 2023. - Llerena Ponce, Elian Jessy (2024)
The case study titled “Advertising strategies in Llerena commercial in the city of Babahoyo in 2023”, its main commercial activity is determined through the marketing of bicycles, motorcycles and articles in general. increase your first objective is your percentage of sales and involve strategies that can help those such as advertising by presenting billboards, posters or flyers where we can expand our commercial brand within the city of Babahoyo or outside it, complying with the established parameters by the Ministry of Labor, working with an established order in all our work activities and maintaining fundamental values based on associable prices that attract customer attention, we will also apply hypothetical-deductive / analytical - synthetic methods, which will help us to impart the respective results for the development of this case study, the techniques that were applied are the following: the survey and interview technique for the following: The case study is complying under the parameters established by the Technical University of Babahoyo for which we have identified one of the rare factors that a company should not have, the lack of marketing and advertising which has become a serious problem for the COMERCIAL LLERENA, this has greatly influenced the sales periods, and has caused dissatisfaction among customers who come from different places in the city to make their purchases at the establishment, also the lack of a means of transportation for their respective marketing, and to become the only business where consumers can go and search for the good or service they request in a unique and indispensable way.